O PROCESSO INTEGRADOR DE PLANEJAMENTO DE VENDAS E OPERAÇÕES PARA O SINCRONISMO E ALINHAMENTO DINÂMICO NA GESTÃO DA CADEIA DE SUPRIMENTOS - Pimentel, Leonardo Bezerra (2015)
The Supply Chain Management (SCM) has been breaking grounds inside companies, becoming the Value Chain Management and consolidating a chain of more intense, dynamic and collaborative relationships. This new context requires management to have a broader view, as to support the decision-making process in the levels of planning, execution and sustainability of business procedures. The present work aims to understanding the system of integration in the supply chain, its benefits, obstacles and advances in the area of Supply Chain Managements (SCM). Besides, the main purpose of this research is to discuss one model of vertical alignment within a company, known as Sales and Operations Planning (S&OP). This work uses speech analysis as a technique to approach articles in the literature, as the bibliometric method concerns. Furthermore, this is an exploratory, descriptive and explanatory study. As a result, it presents concepts of SCM, Supply Chain Integration - SCI, Vertical Alignment, Value Chain Management - VCM and S&OP, all interrelated. It is possible to notice that, through the process of S&OP, the strategy of the company can be spread throughout the whole organization. That allows the company to set its future scenarios and define the actions required so that strategic goals can be achieved in medium and long-term, allowing tactic process to become operational ones. The literature suggests that S&OP promotes profitable growth, increased profit margins and the maximization of the use of assets, making logistical operation more and more efficient. The understanding about the relationship between Value Chain Management (VCM) with the Supply Chain Integration, both inside and outside companies, has been the focus of the present study.